EPC Agenda 2004-03-04 - Academic Senate:::::::::
Educational Policies Committee. Approval of agenda. Approval of Minutes of 5/12/11. Chair Report. Proposed membership change to Senate Diversity Subcommittee approved for Senate agenda. President Report. Proposed Constitutional Change for the Chair Structure approved for Senate agenda. Provost statement. Vice President of SAEM Report. Digital Signatures on Curricular Forms presentation to the Senate not needed. Chair-Elect Report. Vice President of Administration and Finance Report. APC Report. EPC Report. FSAC Report. SAC Report. CFA Report. Associated Students Report. Senate agenda approved.